Adenovirus 12 nononcogenic mutants: oncogenicity of transformed cells and viral proteins synthesized in vivo and in vitro. - Mak, I (1984)
Several nononcogenic cyt mutants of adenovirus type 12 induced the same E1A (55,000 [55K] and 25K) and E1B polypeptides (55K, 19K, and 17K) as did the wild-type virus, except that cyt 68 did not induce the E1B 19K protein. Tumorigenicity tests showed cells transformed by cyt 68 to be highly oncogenic in vivo. Therefore, it was concluded that the E1B 19K polypeptide is not necessary for tumor induction but may be involved in the efficiency of transformation.